Analisis Penyebab Kerusakan Perkerasan Jalan Beton Di Ruas Jalan Darmo Sugondo Gresik - Sapto Budi Wasono; Atik Wahyuni; Adhi Muhtadi (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2020)
Kapten Darmo Sugondo Street daily passed by heavy vehicles which are road access to and leave the Port area in Gresik. Increasing road pavement on Jalan Kapten Darmo Sugondo is absolutely necessary to repair damaged old road pavement to facilitate the flow the transfer of passengers and goods, therefore an increase in road pavement must be in accordance with established standards. from the results of the analysis, it is obtained from the location of point 1 with a plate thickness of 25 cm, it turns out the number of fatique 30 <100% (OK), at the location of point 2 it turns out the quantity of 19.504> 100% (not OK) concrete quality 191 kg /cm2. So the concrete plate thickness is insufficient and this damage happened. Because the thickness and quality of the concrete are not comparable to the heavy vehicles if the heavy vehicles passed daily as long as age of the plan.